Value preferences and academic performance in pre-university students of Huanuco 2020 - Acencio-Malpartida, Larry F. (2021)
This study was of the quantitative type of correlal level, with the aim of analyzing the relationship between valoral preferences and academic performance in pre-university students 2020, the population consisted of 213 students in 4 areas of preparation of the Pre-University Academy of the Municipality of Huánuco, with a sample of 73 subjects who were chosen non-randomly, for convenience and in compliance with the proposed inclusion criteria, the psychometrics technique was used for the collection of data with Escobar's Values and Anti-Values (Valanti) instrument (2001), and the academic record of the 2 preparation examination drills conducted by students; this data was statistically analyzed with the SPSS version 25.0 program; Peace, Truth and Love values could be found to have a distribution of 25%, 26% and 32% respectively in students and at the academic performance level 60.3% are in the deficient category; but it was mainly found that there is a correlation between valoral preferences and academic performance, with a Spearman Rho coefficient of (,279 and p – value ,017 s p<0.05); which tells us a weak level of correlation; being able to conclude that our reality reflects the results obtained at the academic level in international tests such as PISA, but also confirms that the preference of values and academic performance are related to a weak level, being necessary the intervention of other factors that favor an ideal academic performance.